2003
DOI: 10.1046/j.1528-1157.2003.22702.x
|View full text |Cite
|
Sign up to set email alerts
|

Ih Blockers Have a Potential of Antiepileptic Effects

Abstract: Summary:Purpose: The h current (Ih) is an inwardly mixed cationic conductance activated by membrane hyperpolarization and distributed predominantly in the apical dendrites of hippocampal pyramidal neurons. To verify a hypothesis that an anomalous hyperpolarization generates an abnormal excitation by way of Ih channels, we examined the effects of Ih blockers (CsCl and ZD7288) on electrically induced paroxysmal discharges (PADs).Methods: Fifty-three adult male rabbits were used. We measured the PAD threshold eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…We previously demonstrated that CsCl and ZD7288 increased the threshold of electrically induced paroxysmal discharge in the rabbit hippocampus CA1 region [19]. In the present study, oral administration of CsCl or ZD7288 to Mongolian gerbils decreased not only the frequency but also the severity of their inherited epilepsy.…”
Section: Ih Channels and Epileptogenesissupporting
confidence: 63%
See 4 more Smart Citations
“…We previously demonstrated that CsCl and ZD7288 increased the threshold of electrically induced paroxysmal discharge in the rabbit hippocampus CA1 region [19]. In the present study, oral administration of CsCl or ZD7288 to Mongolian gerbils decreased not only the frequency but also the severity of their inherited epilepsy.…”
Section: Ih Channels and Epileptogenesissupporting
confidence: 63%
“…However, studies indicate that HCN1 and HCN2 are most prevalent in the cortex and hippocampus of rats [29], that Ih channel density is highest in the apical dendritic layer of the rat hippocampus CA1 [42], and that HCN1 mRNA is expressed at high levels in the mouse hippocampus CA1 region [37]. In a previous study in which the Ih blockers CsCl and ZD7288 were injected into the stratum radiatum or lacunosum-moleculare in the hippocampus CA1, we found that CsCl and ZD7288 increased the threshold of electrically induced paroxysmal discharge [19]. These findings suggest that Ih channels are present in the hippocampus of Mongolian gerbils.…”
Section: Effects Of Ih Blockers On the Inherited Epilepsy In Mongoliamentioning
confidence: 63%
See 3 more Smart Citations